High temperature resistant super hydrophobic long-acting anticorrosion coating and preparation method thereof

By introducing modified nanoparticles and superhydrophobic silica into epoxy vinyl resin, the crosslinking and hydrophobicity of the coating are improved, and the problems of insufficient corrosion resistance and poor heat resistance of the existing epoxy resin coating in high temperature and strong corrosion environments are solved, and a coating with long-term corrosion resistance, high temperature resistance and excellent mechanical properties are achieved.

CN118995011BActive Publication Date: 2025-03-28淄博德泰新材料科技有限公司 +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411486998.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-28
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing epoxy resin anti-corrosion coatings show insufficient corrosion resistance, poor heat resistance and poor mechanical properties in high temperature and strong corrosion environments, resulting in limited application range in chemical production.

Method used

By introducing modified nanoparticles and superhydrophobic silica into the epoxy vinyl resin, the crosslinking degree, heat resistance, shielding and toughness of the coating are improved by grafting reactions, and the hydrophobicity of the coating is improved by the modified resin.

Benefits of technology

The coating has long-term corrosion resistance, high temperature resistance and excellent mechanical properties. The water contact angle is greater than 150°, and its acid resistance, alkali resistance, salt spray resistance and heat resistance exceed 2,000 hours, and its impact resistance is also significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of anticorrosive coatings, and in particular to high temperature resistant super hydrophobic long-acting anticorrosive coatings and preparation methods thereof. The preparation method of the high temperature resistant super hydrophobic long-acting anticorrosive coating, surface modification of nanoparticles using γ-methacryloxypropyltrimethoxysilane, obtains modified nanoparticles; surface modification of nano silicon dioxide using vinyltrimethoxysilane, obtains super hydrophobic silicon dioxide; modified nanoparticles, super hydrophobic silicon dioxide and methacrylic acid are polymerized, and then grafted onto phenolic epoxy resin by ring-opening reaction, to obtain modified epoxy vinyl resin; modified epoxy vinyl resin and curing agent are uniformly mixed, sprayed onto the surface of metal substrate, and high temperature resistant super hydrophobic long-acting anticorrosive coating is obtained after curing. The present invention not only improves the crosslinking degree, heat resistance, shielding and toughness of epoxy vinyl resin, but also improves the hydrophobicity of coating, so that coating has long-acting anticorrosive property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a high-temperature resistant super-hydrophobic long-acting anti-corrosion coating and a preparation method thereof. Background Art

[0002] Anti-corrosion coating is a coating that can resist erosion by environmental media (such as moisture, oxygen, chemicals, etc.) and protect the substrate from corrosion. It is a coating that is widely used in chemical, transportation, energy, marine engineering and other fields.

[0003] In the chemical industry, most production equipment needs to be exposed to strong corrosive media such as acids, alkalis, and salts, as well as high temperature conditions, which puts strict requirements on the anti-corrosion of equipment. At present, the research on anti-corrosion coatings is gradually developing towards diversification. First, it is necessary to improve the corrosion resistance of coatings in various corrosive environments, such as resistance to chemical media, salt water, salt spray, moisture and heat, oil, mildew, atmospheric aging, alkali, potassium, brine corrosion, etc.; second, the anti-corrosion coating needs to have good bonding with the substrate; third, the anti-corrosion coating also needs to have good physical and mechanical properties, such as low shrinkage, appropriate hardness, good toughness, wear resistance, high temperature resistance, etc.; fourth, in order to extend the service life and maintenance cycle of equipment, the long-term anti-corrosion of anti-corrosion coatings has also become a research focus.

[0004] Among various anti-corrosion coatings, epoxy resin coating has good chemical resistance and can resist the erosion of chemical substances such as acids, alkalis, and solvents. In addition, the raw materials are easily available and the operation is convenient. It is one of the commonly used anti-corrosion coatings in chemical production. In the prior art, fillers and additives are generally added to improve the shielding property of epoxy resin coatings, thereby improving their corrosion resistance. For example, the epoxy resin anti-corrosion coating disclosed in patent CN117887336A improves its corrosion resistance by adding modified montmorillonite and modified zeolite to bisphenol F epoxy resin and trihydroxyphenylmethane epoxy resin; however, this technical solution only improves the corrosion resistance of the coating to a limited extent by adding fillers. Its acid and alkali corrosion resistance is greater than 700h, and it does not achieve long-term corrosion protection. In addition, this technical solution does not improve the heat resistance and mechanical properties of the coating, resulting in a limited scope of application.

[0005] Patent CN108003753A discloses a super hydrophobic long-term anticorrosion coating, which improves the hydrophobicity of the coating by setting a silicone modified epoxy resin bottom layer and a self-cleaning super hydrophobic surface layer, thereby improving its corrosion resistance, and the neutral salt spray test time is greater than 1200h. Patent CN108441085A discloses a super double-repellent long-term anticorrosion coating, which improves the double repellency of the coating by setting a water-based epoxy bottom layer and a super double-repellent fluorine silicon surface layer, thereby improving its corrosion resistance, and the neutral salt spray test time is greater than 1500h. The above technical solutions all achieve the long-term corrosion resistance of the coating, but the double-layer spraying may cause the bonding force between the coatings to decrease, and the spraying thickness of the surface layer is only 10-20μm, which is easily damaged by friction when used in chemical production, which will affect the overall hydrophobicity of the coating, thereby affecting the corrosion resistance of the coating.

[0006] Therefore, in view of the working conditions faced by chemical production, it is necessary to design an epoxy resin anti-corrosion coating with long-term corrosion resistance and heat resistance and excellent comprehensive mechanical properties. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-temperature resistant super-hydrophobic long-lasting anti-corrosion coating, in which modified nanoparticles are introduced into epoxy vinyl resin by a grafting reaction, thereby improving the crosslinking degree, heat resistance, shielding property and toughness of the epoxy vinyl resin, and by modifying the epoxy vinyl resin, the hydrophobicity of the coating is improved, so that the coating has long-lasting anti-corrosion properties; the present invention also provides a preparation method thereof.

[0008] The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating of the present invention comprises the following steps:

[0009] (1) Preparation of modified nanoparticles: dispersing the nanoparticles in a water-alcohol mixture, adding hydrochloric acid to adjust the pH value to 3-4, then adding γ-methacryloxypropyltrimethoxysilane, stirring, separating the solid, and drying to obtain modified nanoparticles;

[0010] (2) Preparation of super-hydrophobic silica: disperse nano-silica in anhydrous ethanol, add ammonia water to adjust the pH value to 9-10, then add vinyltrimethoxysilane, stir, separate the solid, and dry to obtain super-hydrophobic silica;

[0011] (3) Preparation of modified epoxy vinyl resin: firstly, modified nanoparticles, superhydrophobic silica and part of methacrylic acid are used as raw materials, and a polymerization reaction is carried out under the action of an initiator, and then hydroquinone, as well as phenolic epoxy resin, the remaining part of methacrylic acid and a catalyst are added to carry out a ring-opening reaction, and finally maleic anhydride and styrene are added, and the reaction is continued until the acid value of the system is ≤10mgKOH / g, and tert-butyl catechol is added, and the temperature is lowered to obtain a modified epoxy vinyl resin;

[0012] (4) Preparation of long-term anti-corrosion coating: The modified epoxy vinyl resin and the curing agent are mixed evenly and sprayed onto the surface of the metal substrate. After curing, a high-temperature resistant super-hydrophobic long-term anti-corrosion coating is obtained.

[0013] In step (1), the nanoparticles are one or more of montmorillonite, attapulgite, carbon nanotubes, and kaolin; and the mass ratio of the nanoparticles to γ-methacryloxypropyltrimethoxysilane is 1:(0.08-0.12).

[0014] In step (1), the water-alcohol mixture is a mixture of water and ethanol in a volume ratio of 1:(3-4); the concentration of γ-methacryloxypropyltrimethoxysilane in the water-alcohol mixture is 5-8wt.%.

[0015] The water-alcohol mixture is more conducive to the dispersion and reaction of γ-methacryloxypropyltrimethoxysilane. The hydrolyzed groups of γ-methacryloxypropyltrimethoxysilane chemically bond with the hydroxyl groups on the surface of the nanoparticles, introducing organic molecular chains on the surface of the nanoparticles, thereby improving the dispersibility and stability of the nanoparticles in the organic medium. At the same time, double bond reactive groups and hydrophobic segments are introduced on the surface of the nanoparticles.

[0016] In step (2), the mass ratio of nano-silicon dioxide to vinyltrimethoxysilane is 1:(8-10); the concentration of nano-silicon dioxide in anhydrous ethanol is 0.5-0.8wt.%.

[0017] The invention utilizes vinyltrimethoxysilane to modify nano silicon dioxide. Nano silicon dioxide dissolved in ethanol is easily hydrolyzed to form a large number of hydroxyl groups on the surface. During the modification process, the hydroxyl groups on the surface of the nano silicon dioxide undergo a condensation reaction with the methoxy groups on the vinyltrimethoxysilane, and the vinyltrimethoxysilane is grafted onto the surface of the nano silicon dioxide. A nano silicon dioxide molecule has a plurality of hydroxyl groups on its surface, and a plurality of vinyltrimethoxysilanes can be grafted onto the surface, thereby giving the nano silicon dioxide super hydrophobicity. Meanwhile, the introduction of double bonds enables the nano silicon dioxide to have a certain reaction ability.

[0018] In step (3), the molar ratio of the carboxyl groups contained in the methacrylic acid to the epoxy groups contained in the phenolic epoxy resin is 1:(1-1.05); the molar ratio of the carboxyl groups contained in the maleic anhydride to the epoxy groups contained in the phenolic epoxy resin is 1:(0.04-0.06).

[0019] In step (3), the amount of the modified nanoparticles is 5-8% of the total mass of the phenolic epoxy resin and methacrylic acid; the amount of the superhydrophobic silica is 10-12% of the total mass of the phenolic epoxy resin and methacrylic acid; in the polymerization reaction, the mass ratio of the total mass of the modified nanoparticles and the superhydrophobic silica to the mass of methacrylic acid is 1:(1-1.2).

[0020] In step (3), the initiator is azobisisobutyronitrile; in the polymerization reaction, the amount of the initiator added is 0.05-0.1% of the total mass of the modified nanoparticles, superhydrophobic silica, and methacrylic acid; the polymerization temperature is 100-110°C, and the polymerization time is 1-2h. The polymerization reaction can be carried out in an organic solvent, such as toluene, and the organic solvent needs to be distilled off after the reaction. The amount of initiator added and the polymerization time should be strictly controlled in the polymerization reaction to obtain a modified polymer with a small molecular weight.

[0021] The double bonds contained in the organic chains introduced on the surfaces of the modified nanoparticles and super-hydrophobic silica undergo a polymerization reaction with methacrylic acid, thereby introducing the modified nanoparticles and super-hydrophobic silica into the methacrylic acid molecular chain by chemical bonding. During the reaction of the phenolic epoxy resin and methacrylic acid, the modified nanoparticles and super-hydrophobic silica are grafted onto the epoxy vinyl resin molecular chain, which can make the modified nanoparticles and super-hydrophobic silica more evenly and firmly combined in the epoxy vinyl resin system. The toughness and barrier properties of the coating are increased by the grafting of the modified nanoparticles and super-hydrophobic silica; the crosslinking density of the epoxy vinyl resin system can also be improved; the modified nanoparticles and super-hydrophobic silica can fill the micropores of the epoxy vinyl resin coating, thereby improving the compactness and heat resistance of the coating; and the stable grafting of the super-hydrophobic silica can give the epoxy vinyl resin excellent hydrophobicity.

[0022] In step (3), the amount of hydroquinone used is 0.02-0.03% of the total mass of the phenolic epoxy resin and methacrylic acid; the amount of tert-butyl catechol used is 0.01-0.02% of the total mass of the phenolic epoxy resin and methacrylic acid.

[0023] Both hydroquinone and tert-butylcatechol are used as polymerization inhibitors to prevent the double bonds from self-polymerizing after the ring-opening reaction and the reaction. Among them, hydroquinone has a higher polymerization inhibition effect under high temperature conditions. Adding hydroquinone after the polymerization reaction can, on the one hand, terminate the polymerization reaction of the modified nanoparticles and methacrylic acid to obtain a low molecular weight polymer intermediate, and on the other hand, prevent the double bonds from self-polymerizing in the ring-opening reaction; tert-butylcatechol has a better low-temperature polymerization inhibition effect. Adding it after the reaction can greatly improve the polymerization inhibition effect of epoxy vinyl resin during use.

[0024] In step (3), the catalyst is one of benzyltriethylammonium chloride and tetrabutylammonium chloride; the amount of the catalyst is 0.2-0.3% of the total mass of the phenolic epoxy resin and methacrylic acid; the ring-opening reaction temperature is 100-110° C., and the ring-opening reaction time is 3-5 h.

[0025] In step (3), the amount of styrene used is 34-36% of the total mass of the phenolic epoxy resin and methacrylic acid.

[0026] In step (4), the curing agent is one of methyl ethyl ketone peroxide and cyclohexanone peroxide; the amount of the curing agent is 1-2% of the mass of the modified epoxy vinyl resin.

[0027] In step (4), the curing time is 24-48 hours.

[0028] The present invention also provides a high temperature resistant super hydrophobic long-acting anticorrosion coating prepared by the above preparation method, with a water contact angle greater than 150°, acid resistance (5wt.% H2SO4)>1500h, alkali resistance (10wt.% NaOH)>1300h, salt spray resistance (50wt.% NaCl)>2000h, heat resistance (120°C)>2000h, and impact resistance>50cm.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention uses γ-methacryloxypropyltrimethoxysilane to modify the surface of nanoparticles, and introduces double-bond hydrophobic organic molecular chains on the surface of nanoparticles by chemical bonding, thereby improving the dispersibility and stability of the nanoparticles in the organic medium and giving the nanoparticles certain hydrophobicity and reactivity;

[0031] (2) The present invention uses vinyl trimethoxy silane to modify nano-silica, and grafts multiple vinyl trimethoxy silanes on the surface of a nano-silica molecule, thereby giving the nano-silica super-hydrophobicity and reactivity;

[0032] (3) The present invention allows the double bonds contained in the organic chains introduced on the surfaces of the modified nanoparticles and super-hydrophobic silica to undergo a polymerization reaction with methacrylic acid, thereby introducing the modified nanoparticles and super-hydrophobic silica into the methacrylic acid molecular chain by chemical bonding, and further grafting them onto the epoxy vinyl resin molecular chain, so that the modified nanoparticles and super-hydrophobic silica can be more evenly and firmly combined in the epoxy vinyl resin system, thereby increasing the toughness and barrier properties of the coating, improving the crosslinking density of the epoxy vinyl resin system, improving the compactness and heat resistance of the coating, and giving the epoxy vinyl resin excellent hydrophobicity;

[0033] (4) The present invention uses a multifunctional phenolic epoxy resin to prepare an epoxy vinyl resin, and adds double-bond-containing maleic anhydride in the later stage of the reaction, which can increase the cross-linking density of the coating and enhance its corrosion resistance and high temperature resistance;

[0034] (5) The high temperature resistant super hydrophobic long-lasting anticorrosion coating prepared by the present invention has a water contact angle greater than 150° and has excellent water resistance. The super hydrophobic surface can form a flowing air isolation between the corrosive medium and the coating surface, thereby further improving the corrosion resistance and achieving a long-lasting anticorrosion effect. At the same time, the anticorrosion coating increases the crosslinking degree of the resin molecular chain by introducing modified nanoparticles, super hydrophobic silica and maleic anhydride into the resin molecular chain, thereby greatly improving the heat resistance and impact resistance of the anticorrosion coating. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with the examples. The phenolic epoxy resin used in the examples is of type F51, and the remaining raw materials are all commercially available conventional raw materials. Example

[0036] The high temperature resistant super hydrophobic long-lasting anticorrosion coating was prepared by the following method:

[0037] (1) Preparation of modified nanoparticles: Nano-montmorillonite particles are dispersed in a mixture of water and ethanol in a volume ratio of 1:3, hydrochloric acid is added to adjust the pH value to 4, and then γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-montmorillonite particles to γ-methacryloxypropyltrimethoxysilane is 1:0.1, and the concentration of γ-methacryloxypropyltrimethoxysilane in the mixture is 6 wt.%, and the mixture is stirred at 50° C., the solid is separated, and dried to obtain modified nanoparticles;

[0038] (2) Preparation of super-hydrophobic silica: Nano-silica was dispersed in anhydrous ethanol, the concentration of nano-silica in the anhydrous ethanol was 0.6 wt.%, ammonia was added to adjust the pH value to 10, and then vinyl trimethoxy silane was added, the mass ratio of nano-silica to vinyl trimethoxy silane was 1:10, stirred at 40°C, the solid was separated, and dried to obtain super-hydrophobic silica;

[0039] (3) Preparation of modified epoxy vinyl resin:

[0040] The materials are prepared according to the following ratio: the molar ratio of the carboxyl group contained in methacrylic acid to the epoxy group contained in the novolac epoxy resin is 1:1, the molar ratio of the carboxyl group contained in maleic anhydride to the epoxy group contained in the novolac epoxy resin is 1:0.05, the mass of the modified nanoparticles is 6% of the total mass of the novolac epoxy resin and methacrylic acid, the mass of the superhydrophobic silica is 12% of the total mass of the novolac epoxy resin and methacrylic acid, and the mass of styrene is 34% of the total mass of the novolac epoxy resin and methacrylic acid;

[0041] First, modified nanoparticles, super-hydrophobic silica and part of methacrylic acid are used as raw materials, wherein the total mass ratio of the modified nanoparticles and the super-hydrophobic silica to the mass ratio of methacrylic acid is 1:1, and the modified nanoparticles, super-hydrophobic silica, and 0.08% of the total mass of methacrylic acid as initiator azobisisobutyronitrile are added, and the temperature is raised to 105° C. to carry out polymerization reaction for 1.5 hours; then, phenolic epoxy resin, 0.03% of the total mass of methacrylic acid as hydroquinone, and phenolic epoxy resin, the remaining part of methacrylic acid and phenolic epoxy resin, 0.3% of the total mass of methacrylic acid as catalyst benzyltriethylammonium chloride are added, and the temperature is raised to 105° C. to carry out ring-opening reaction for 4 hours, and finally maleic anhydride and styrene are added, and the reaction is continued until the acid value of the system is ≤10 mgKOH / g, and tert-butyl catechol of 0.01% of the total mass of phenolic epoxy resin and methacrylic acid is added, and the temperature is lowered to obtain a modified epoxy vinyl resin;

[0042] (4) Preparation of long-lasting anti-corrosion coating: Add 1.5% methyl ethyl ketone peroxide to the modified epoxy vinyl resin, mix well, and spray it onto the surface of the metal substrate. After curing, a high-temperature resistant super-hydrophobic long-lasting anti-corrosion coating is obtained. Example

[0043] The high temperature resistant super hydrophobic long-lasting anticorrosion coating was prepared by the following method:

[0044] (1) Preparation of modified nanoparticles: Carbon nanotube particles are dispersed in a mixture of water and ethanol in a volume ratio of 1:4, hydrochloric acid is added to adjust the pH value to 3, and then γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-montmorillonite particles to γ-methacryloxypropyltrimethoxysilane is 1:0.12, and the concentration of γ-methacryloxypropyltrimethoxysilane in the mixture is 5wt.%, and the mixture is stirred at 50°C, the solid is separated, and dried to obtain modified nanoparticles;

[0045] (2) Preparation of super-hydrophobic silica: Nano-silica was dispersed in anhydrous ethanol, the concentration of nano-silica in the anhydrous ethanol was 0.5 wt.%, ammonia was added to adjust the pH value to 10, and then vinyl trimethoxy silane was added, the mass ratio of nano-silica to vinyl trimethoxy silane was 1:9, stirred at 40°C, the solid was separated, and dried to obtain super-hydrophobic silica;

[0046] (3) Preparation of modified epoxy vinyl resin:

[0047] The materials are prepared according to the following ratio: the molar ratio of the carboxyl group contained in methacrylic acid to the epoxy group contained in the novolac epoxy resin is 1:1.02, the molar ratio of the carboxyl group contained in maleic anhydride to the epoxy group contained in the novolac epoxy resin is 1:0.06, the mass of the modified nanoparticles is 5% of the total mass of the novolac epoxy resin and methacrylic acid, the mass of the superhydrophobic silica is 10% of the total mass of the novolac epoxy resin and methacrylic acid, and the mass of styrene is 35% of the total mass of the novolac epoxy resin and methacrylic acid;

[0048] First, modified nanoparticles, super-hydrophobic silica and part of methacrylic acid are used as raw materials, wherein the total mass ratio of the modified nanoparticles and the super-hydrophobic silica to the mass ratio of methacrylic acid is 1:1.1, and the modified nanoparticles, super-hydrophobic silica, and 0.06% of the total mass of methacrylic acid as initiator azobisisobutyronitrile are added, and the temperature is raised to 100° C. to carry out polymerization reaction for 2 hours; then, phenolic epoxy resin, 0.02% of the total mass of methacrylic acid as hydroquinone, and phenolic epoxy resin, the remaining part of methacrylic acid and phenolic epoxy resin, 0.25% of the total mass of methacrylic acid as catalyst tetrabutylammonium chloride are added, and the temperature is raised to 100° C. to carry out ring-opening reaction for 5 hours, and finally maleic anhydride and styrene are added, and the reaction is continued until the acid value of the system is ≤10 mgKOH / g, and 0.02% of the total mass of phenolic epoxy resin and tert-butyl catechol is added, and the temperature is lowered to obtain a modified epoxy vinyl resin;

[0049] (4) Preparation of long-lasting anti-corrosion coating: Add 2% methyl ethyl ketone peroxide to the modified epoxy vinyl resin, mix well, and spray it onto the surface of the metal substrate. After curing, a high-temperature resistant super-hydrophobic long-lasting anti-corrosion coating is obtained. Example

[0050] The high temperature resistant super hydrophobic long-lasting anticorrosion coating was prepared by the following method:

[0051] (1) Preparation of modified nanoparticles: Nano-montmorillonite particles were dispersed in a mixture of water and ethanol in a volume ratio of 1:3.5, hydrochloric acid was added to adjust the pH value to 4, and then γ-methacryloxypropyltrimethoxysilane was added, wherein the mass ratio of nano-montmorillonite particles to γ-methacryloxypropyltrimethoxysilane was 1:0.08, and the concentration of γ-methacryloxypropyltrimethoxysilane in the mixture was 8 wt.%, and the mixture was stirred at 50°C, the solid was separated, and dried to obtain modified nanoparticles;

[0052] (2) Preparation of super-hydrophobic silica: Nano-silica was dispersed in anhydrous ethanol, the concentration of nano-silica in the anhydrous ethanol was 0.8 wt.%, ammonia was added to adjust the pH value to 9, and then vinyl trimethoxysilane was added, the mass ratio of nano-silica to vinyl trimethoxysilane was 1:8, stirred at 40°C, the solid was separated, and dried to obtain super-hydrophobic silica;

[0053] (3) Preparation of modified epoxy vinyl resin:

[0054] The materials are prepared according to the following ratio: the molar ratio of the carboxyl group contained in methacrylic acid to the epoxy group contained in the novolac epoxy resin is 1:1.05, the molar ratio of the carboxyl group contained in maleic anhydride to the epoxy group contained in the novolac epoxy resin is 1:0.04, the mass of the modified nanoparticles is 8% of the total mass of the novolac epoxy resin and methacrylic acid, the mass of the superhydrophobic silica is 11% of the total mass of the novolac epoxy resin and methacrylic acid, and the mass of styrene is 36% of the total mass of the novolac epoxy resin and methacrylic acid;

[0055] First, modified nanoparticles, super-hydrophobic silica and part of methacrylic acid are used as raw materials, wherein the total mass ratio of the modified nanoparticles and the super-hydrophobic silica to the mass ratio of methacrylic acid is 1:1.2, and the modified nanoparticles, super-hydrophobic silica, and 0.05% of the total mass of methacrylic acid as initiator azobisisobutyronitrile are added, and the temperature is raised to 110° C. to carry out polymerization reaction for 1 hour; then, phenolic epoxy resin, 0.025% of the total mass of methacrylic acid as hydroquinone, and phenolic epoxy resin, the remaining part of methacrylic acid and phenolic epoxy resin, 0.2% of the total mass of methacrylic acid as catalyst benzyltriethylammonium chloride are added, and the temperature is raised to 110° C. to carry out ring-opening reaction for 3 hours, and finally maleic anhydride and styrene are added, and the reaction is continued until the acid value of the system is ≤10 mgKOH / g, and tert-butyl catechol of 0.015% of the total mass of phenolic epoxy resin and methacrylic acid is added, and the temperature is lowered to obtain a modified epoxy vinyl resin;

[0056] (4) Preparation of long-lasting anti-corrosion coating: Add 1% cyclohexanone peroxide to the modified epoxy vinyl resin, mix well, and spray it onto the surface of the metal substrate. After curing, a high-temperature resistant super-hydrophobic long-lasting anti-corrosion coating is obtained.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 1 is that no modified nanoparticles are added when preparing the modified epoxy vinyl resin in step (3).

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 1 is that no super-hydrophobic silica is added when preparing the modified epoxy vinyl resin in step (3).

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 1 is that, in step (3), no modified nanoparticles and super-hydrophobic silica are added when preparing the epoxy resin, and the modified nanoparticles and super-hydrophobic silica added in step (3) are placed in step (4), added to the coating in a blended manner, and sprayed to prepare the coating.

[0063] The long-lasting anti-corrosion coating prepared in each embodiment and comparative example was subjected to performance tests, and the coating thickness was 100 μm, wherein the water contact angle was tested using a contact angle tester; the adhesion was tested with reference to the standard GB / T 9286-2014; the acid resistance and alkali resistance were tested with reference to the standard GB / T 9274-1988; the heat resistance was tested with reference to the standard GB / T 1735-2009; the salt spray resistance was tested with reference to the standard GB / T 1771-2007; and the impact resistance was tested with reference to the standard GB / T 1732-2020.

[0064] The long-term anticorrosion coating prepared by the present invention has a water contact angle greater than 150°, acid resistance>1500h, alkali resistance>1300h, salt spray resistance>2000h, heat resistance>2000h, impact resistance>50cm, and has excellent corrosion resistance, high temperature resistance and mechanical properties. Comparative Examples 1 and 2 respectively reduce the addition of modified nanoparticles and super-hydrophobic silica, which on the one hand leads to a decrease in the crosslinking density of the epoxy vinyl resin, thereby reducing its shielding, heat resistance and mechanical properties, and on the other hand leads to a decrease in the number of hydrophobic segments in the coating. The reduction in the hydrophobicity of the coating also causes a decrease in the corrosion resistance, especially the reduction in super-hydrophobic silica, which has a greater impact on the hydrophobicity of the coating. In Comparative Example 3, the modified nanoparticles and super-hydrophobic silica are added to the coating by blending rather than chemical bonding, which will reduce the cross-linking density of the epoxy vinyl resin molecular chain, resulting in a decrease in its shielding, heat resistance and mechanical properties. Moreover, blending is not conducive to the uniform dispersion and stable combination of the modified nanoparticles and super-hydrophobic silica, which directly affects the long-term corrosion resistance of the coating.

Claims

1. A method for preparing a high temperature resistant super hydrophobic long-acting anticorrosion coating, characterized in that: The following steps are involved: (1) Preparation of modified nanoparticles: dispersing the nanoparticles in a water-alcohol mixture, adding hydrochloric acid to adjust the pH value to 3-4, then adding γ-methacryloxypropyltrimethoxysilane, stirring, separating the solid, and drying to obtain modified nanoparticles; (2) Preparation of super-hydrophobic silica: disperse nano-silica in anhydrous ethanol, add ammonia water to adjust the pH value to 9-10, then add vinyltrimethoxysilane, stir, separate the solid, and dry to obtain super-hydrophobic silica; (3) Preparation of modified epoxy vinyl resin: firstly, modified nanoparticles, superhydrophobic silica and part of methacrylic acid are used as raw materials, and a polymerization reaction is carried out under the action of an initiator, and then hydroquinone, as well as phenolic epoxy resin, the remaining part of methacrylic acid and a catalyst are added to carry out a ring-opening reaction, and finally maleic anhydride and styrene are added, and the reaction is continued until the acid value of the system is ≤10mgKOH / g, and tert-butyl catechol is added, and the temperature is lowered to obtain a modified epoxy vinyl resin; (4) Preparation of long-term anti-corrosion coating: The modified epoxy vinyl resin and the curing agent are mixed evenly, and sprayed onto the surface of the metal substrate. After curing, a high-temperature resistant super-hydrophobic long-term anti-corrosion coating is obtained; In step (1), the nanoparticles are one or more of montmorillonite, attapulgite, carbon nanotubes, and kaolin; the mass ratio of the nanoparticles to γ-methacryloxypropyltrimethoxysilane is 1:(0.08-0.12); In step (2), the mass ratio of nano-silicon dioxide to vinyltrimethoxysilane is 1:(8-10); the concentration of nano-silicon dioxide in anhydrous ethanol is 0.5-0.8wt.%.

2. The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating according to claim 1, characterized in that: In step (1), the water-alcohol mixture is a mixture of water and ethanol in a volume ratio of 1:(3-4); the concentration of γ-methacryloxypropyltrimethoxysilane in the water-alcohol mixture is 5-8wt.%.

3. The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating according to claim 1, characterized in that: In step (3), the molar ratio of the carboxyl groups contained in the methacrylic acid to the epoxy groups contained in the phenolic epoxy resin is 1:(1-1.05); the molar ratio of the carboxyl groups contained in the maleic anhydride to the epoxy groups contained in the phenolic epoxy resin is 1:(0.04-0.06).

4. The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating according to claim 1, characterized in that: In step (3), the amount of the modified nanoparticles is 5-8% of the total mass of the phenolic epoxy resin and methacrylic acid; the amount of the superhydrophobic silica is 10-12% of the total mass of the phenolic epoxy resin and methacrylic acid; in the polymerization reaction, the mass ratio of the total mass of the modified nanoparticles and the superhydrophobic silica to the mass of methacrylic acid is 1:(1-1.2).

5. The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating according to claim 1, characterized in that: In step (3), the initiator is azobisisobutyronitrile; in the polymerization reaction, the amount of the initiator added is 0.05-0.1% of the total mass of the modified nanoparticles, superhydrophobic silica, and methacrylic acid; the polymerization reaction temperature is 100-110° C., and the polymerization reaction time is 1-2 h; The amount of hydroquinone used is 0.02-0.03% of the total mass of the phenolic epoxy resin and methacrylic acid; the amount of tert-butyl catechol used is 0.01-0.02% of the total mass of the phenolic epoxy resin and methacrylic acid; The catalyst is one of benzyltriethylammonium chloride and tetrabutylammonium chloride; the amount of the catalyst is 0.2-0.3% of the total mass of the phenolic epoxy resin and methacrylic acid; the ring-opening reaction temperature is 100-110° C., and the ring-opening reaction time is 3-5 hours.

6. The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating according to claim 1, characterized in that: In step (3), the amount of styrene used is 34-36% of the total mass of the phenolic epoxy resin and methacrylic acid.

7. The method for preparing the high temperature resistant super hydrophobic long-acting anticorrosion coating according to claim 1, characterized in that: In step (4), the curing agent is one of methyl ethyl ketone peroxide and cyclohexanone peroxide; the amount of the curing agent is 1-2% of the mass of the modified epoxy vinyl resin.

8. A high temperature resistant super hydrophobic long-acting anticorrosion coating, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Self-cleaning super-hydrophobic long-acting anti-corrosion coating and preparation method thereof

    CN108003753A

  • Waterborne super-amphiphobic long-effective anticorrosive coating and preparation method thereof

    CN108441085A

  • Photosensitive resin composition, dry film using same, printed wiring board, and method for producing printed wiring board

    CN104937492A

  • Nano-silica / polyacrylate organic and inorganic hybrid water-dispersible resin and preparation method thereof

    CN105061700A

  • Preparation method of high-heat-resistance phenolic epoxy vinyl resin

    CN115785397A